PENGARUH PROMOSI, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN CAFÉ BERINGIN - Dadi Akhmad Perdana,; Indra Firdiyansyah, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study aims to determine and examine the effect of promotion, brand image and service quality oncustomer loyalty at Cafe Beringin. Data was collected by distributing online-based questionnaires and  with  a  total  of  97  respondents.  This  research  uses  non-probability  sampling  method  with purposive sampling technique. This study uses descriptive quantitative methods, using several tests, namely validity test, reliability test, classical assumption test, multiple linear regression, t test, f test and coefficient of determination. Analysis of the data using the SPSS version of IBM statistics 20. The results of this study obtained the regression equation Y = -0.162 + 0.367X1 + 0.993X2 + 0.062X3 + e. The promotion variable has a significant effect between promotions on customer loyalty with a tcount (4, 264) > ttable (1.98580). Brand image variable has a significant effect between brand image on customer loyalty with a value of tcount (5,162) > ttable (1,98580). The service quality variable has no significant effect on customer loyalty with a value of tcount (0.658) < ttable (1.98580). And the variables of promotion, brand image and service quality have a simultaneous effect on customer loyalty with an Fcount of 90.330 > Ftable of 2.701.